If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 91x = 39x + 11 Reorder the terms: 3 + 91x = 11 + 39x Solving 3 + 91x = 11 + 39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39x' to each side of the equation. 3 + 91x + -39x = 11 + 39x + -39x Combine like terms: 91x + -39x = 52x 3 + 52x = 11 + 39x + -39x Combine like terms: 39x + -39x = 0 3 + 52x = 11 + 0 3 + 52x = 11 Add '-3' to each side of the equation. 3 + -3 + 52x = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 52x = 11 + -3 52x = 11 + -3 Combine like terms: 11 + -3 = 8 52x = 8 Divide each side by '52'. x = 0.1538461538 Simplifying x = 0.1538461538
| 2x^2=3x+12 | | 3a^2+a-10=0 | | 24-6x=12-8x | | (A-3)(3a-1)= | | -3.6r-4.5r=-6.48 | | 5.5+2.2n-4.789n=-3.3026 | | -3.5x+3.3x=0.86 | | 2(3x-4)+3(2x+2)=142 | | (x+5)(y-3)=0 | | 4x+11=-43-5x | | -4.3r-2.2r=13 | | (2z+6)(z-2)= | | m+2.6+0.26=3.76 | | xy+5y-3x=15 | | 4.79n+3.9n=-13.035 | | X-0.80X=5159 | | 20x+55y=92.65 | | 5x+x-10=20-6x | | x(2)+8=24 | | 0.837x-2.1+3.6x=17.498229 | | 3x-22=2-5x | | 3log[5](x*x-17)=log[5](x+3) | | 8-w+6=9w-2 | | Y-14=3y+4 | | 18x^3-14x^2+6x= | | 55-4y=3y+6 | | 2x^2-9xy+9y^2=0 | | 55-4y=3y+4 | | 6x^2+11xy+3y^2=0 | | 8r+4=5r+15 | | R^3+1=0 | | 5(a-6)=40 |